ENDOCANNABINOID SYSTEM AND SICKLE CELL ANEMIA: CNR2 POLYMORPHISM IS ASSOCIATED WITH PRIAPISM - ACM Berti; VS Ramos; LA Souz-Júnior; GA Bernardino; GS Arcanjo; L Gazarini; MAC Bezerra; DGH Silva; E Belin-Júnior (Hematology, Transfusion and Cell Therapy, 2023)
Objectives: Evaluate the association of single nucleotide polymorphisms (SNPs) of the endocannabinoid system (ECS) with the hemolytic and vasculopathy subphenotypes in sickle cell anemia (SCA) patients. Methodology: The study was performed with 297 SCA patients (median age 30 years, range 6 to 66 years, 171 males, 57.6%), enrolled and regularly followed in a reference center in northeast Brazil. Clinical and laboratory data were obtained from medical records. Patients were divided into subgroups according to clinical complications. The control group was patients without complications. Peripheral blood samples from all patients were collected, and genomic DNA was extracted using the phenol-chloroform protocol. The SCA genotype was confirmed with PCR followed by restriction analysis with Dde I, and alpha thalassemia (-α3.7kb) mutation was detected with GAP-PCR. MAGL (rs604300, A>G), FAAH (rs324430, C>A), CNR1 (rs7766029, T>C), and CNR2 (rs35761398, TT>CC) polymorphisms were genotyped using TaqMan assays. Results: Overall, 73 patients developed stroke (24.6%), 80 of the men presented priapism (46.8%), and 144 (48.5%) were assigned as the control group (for priapism, n = 58). Regarding clinical and laboratory data, gender, total hemoglobin (Hb), reticulocyte count, indirect bilirubin, and lactate dehydrogenase were not associated with clinical complications. Lower levels of Hb F (%) were associated with stroke (stroke, Hb F 5 ± 3.3% vs. control group, Hb F 9.6 ± 5.6, p < 0.0001), and the non-mutated genotype for -α3.7kb was associated with priapism (p < 0.0001). Due to a better fit of data, the overdominant model of inheritance was adopted for all SNPs. The TT-CC genotype for CNR2 SNP (33 [42.3%] in the priapism group and 31 [53.4%] in control) was independently associated with priapism, even when -α3.7kb was included as a confounder (OR = 0.386 [0.175 – 0.854], p = 0.019). No statistical association was found for the other SNPs analyzed. Discussion: SCA is an inherited disease characterized by the homozygous genotype of HBB:c.20 T>A mutation, which encodes Hb S. The main determinant of SCA severity is the Hb S polymerization level, leading to hemolysis, vasculopathy, vaso-occlusion, and an inflammatory state. In a quest for new insights into the pathophysiology and therapies in SCA, the ECS posts as a potential candidate once it demonstrates a significant role in several biochemical and physiological pathways of clinical interest. The receptor cannabinoid 2 (CB2), encoded by the CNR2 gene, is mainly expressed in immune cells and plays a crucial role in the regulation of the immune system. Activation of CB2 receptors exerts potent anti-inflammatory effects, reducing the production of pro-inflammatory cytokines such as TNF-α and IL-1β and reducing leukocyte infiltration and migration, decreasing tissue damage and inflammation. In our study, the lower chance of developing priapism associated with the TT-CC genotype for CNR2 demonstrates a potential CB2 effect in regulating SCA complications by modulating inflammation. Conclusion: The genetic and biochemical basis of SCA complications still needs to be completed, and searching for new predictors is essential. Based on CB2 functions and our findings, this gene represents a potential candidate for modulating SCA pathophysiology. Now, it's important to find out how this modulation functionally occurs.